ANALISIS KETERAMPILAN DASAR MENGAJAR GURU KELAS PADA MATA PELAJARAN BAHASA INGGRIS DI SDN TEGAL BESAR 2 - Siti Khusniatul Amalia; Mely Agustin Reni Pitasari; Prima Cristi Crismono (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to describe and analyze the basic teaching skills of english teachers at SDN Tegal Besar 2. The research was motivated by the importance of pedagogical competence as mandated by the Teacher and Lecturer Law, particularly the ability to apply eight components of basic teaching skills. A qualitative descriptive approach was employed, involving observation, interviews, and documentation with english teachers of grades IVa, IVb, Va, Vb, VIa, VIb. Data validity was through triangulation of techniques and sources. The results showed that teachers have generally implemented the eight components of basic teaching skills—opening and closing lessons, explaining, questioning, variation, guiding discussions, reinforcement, classroom management, and evaluation—quite well. The use of concrete methods, educational games, and digital media such as Quizzis and Wordwall contributed positively to students’ motivation and engagement. But in stating learning objectives, variation in activities has not been implemented optimally. Overall, the study concludes that basic teaching skills significantly influence the effectiveness of english learning in elementary schools, and teachers are encouraged to strengthen vocabulary strategies, consistently communicate learning goals, and develop more innovative teaching methods to enhance student learning outcomes.